Preparation method of tetrabasic lead sulfate for lead storage battery
By adopting non-aqueous medium-assisted wet grinding and organic solvent finishing methods in the preparation of tetrabasic lead sulfate, the problems of high energy consumption and poor product morphology in the existing technology are solved, and the efficient preparation of small rod-shaped grains is achieved, thereby improving the cycle life and production efficiency of the battery.
Patent Information
- Application Number
- CN202510755999.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-07
- Publication Date
- 2025-09-12
AI Technical Summary
The existing technology for preparing tetrabasic lead sulfate suffers from high energy consumption, poor product morphology, and low production efficiency. In particular, when preparing it by grinding in an aqueous system, it is difficult to obtain fine rod-shaped grains, and the battery cycle life cannot be significantly improved.
A non-aqueous medium-assisted wet grinding method is used in combination with an organic solvent for short-term crystal modification. The lubricity and dispersibility of organic solvents such as ethylene glycol or polyethylene glycol are utilized in combination with ball milling technology to prepare fine rod-shaped tetrabasic lead sulfate grains.
It achieves low-energy and high-efficiency preparation of small rod-shaped tetrabasic lead sulfate grains, improves the cycle life and production efficiency of the battery, and has few grain defects and excellent morphology.
Smart Images

Figure BDA0005438745850000081
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lead-acid batteries, and in particular to a method for preparing tetrabasic lead sulfate for lead-acid batteries. Background Art
[0002] During the manufacturing process of lead-acid batteries, tribasic lead sulfate (3BS) and tetrabasic lead sulfate (4BS) are often added to the positive electrode lead paste as precursors of the positive electrode active material PbO2. Among them, 4BS has a relatively coarse grain skeleton, which has a significant effect on improving the battery cycle life.
[0003] The current industrial production of tetrabasic lead sulfate primarily relies on hydrothermal synthesis, where stoichiometric lead oxide and sulfuric acid react in aqueous solution to produce rod-shaped 4BS molecules with excellent additive efficiency. Mechanical grinding, a commonly used solid-phase reaction method, produces 4BS by grinding dry lead oxide and lead sulfate at room temperature for a sufficient period of time. However, this method is inferior to hydrothermal reaction in terms of product morphology and production efficiency (due to the long grinding time, continuous production is not possible).
[0004] In fact, from a kinetic perspective, the synthesis of 4BS in water using lead oxide and lead sulfate is unfavorable. Not only does the resulting basic lead sulfate encapsulate the lead oxide, slowing the reaction, but it also easily generates 3BS byproducts containing water of crystallization. Although these problems can be addressed to a certain extent by increasing the reaction temperature, this also leads to increased energy consumption and coarse product grains. For example, Chinese invention patent application number CN109867302A discloses a high-purity, ultrafine tetrabasic lead sulfate product and its preparation method, which requires a hydrothermal reaction at 110-180°C for 1-4 hours to obtain rod-shaped 4BS crystals with an average particle size of approximately 10 μm.
[0005] In contrast, mechanical grinding of aqueous raw materials at room temperature more easily yields 3BS, or, when a significant excess of lead oxide is present, produces relatively coarse 4BS grains, defeating the primary purpose of the grinding method. Some patents attempt to improve this process, such as Chinese invention patent application number CN103928685A, which discloses a method for preparing nano-tetrabasic lead sulfate. This involves grinding excess lead oxide and lead sulfate in water, followed by ultrasonic dispersion to form a slurry, and then drying to produce a nanoscale 4BS product. However, this increases the energy consumption of the ultrasonic step, and the grains lack the elongated structure that improves battery cycle life.
[0006] In addition, some existing technologies use a method of hydrothermal synthesis followed by short-term grinding instead of full grinding. For example, Chinese invention patent application number CN114538503A discloses a method and apparatus for preparing high-purity tetrabasic lead sulfate, which involves further grinding the hydrothermally synthesized 4BS to 1-3 μm.
[0007] In view of the many problems existing in the preparation of 4BS by grinding in aqueous systems, the existing technology requires a preparation method of tetrabasic lead sulfate that combines the kinetic advantages and low overall energy consumption of anhydrous grinding with the high production efficiency and good product morphology of hydrothermal synthesis. Summary of the Invention
[0008] The present invention aims to provide a method for preparing high-purity tetrabasic lead sulfate seed crystals. The method comprises wet grinding the raw materials with the aid of a non-aqueous medium, followed by crystal modification in an organic solvent for a short period of time to obtain fine, rod-shaped 4BS grains. The method has high production efficiency and economy.
[0009] The object of the present invention is to disclose a method for preparing tetrabasic lead sulfate for lead-acid batteries, comprising the following steps:
[0010] S1: The lead oxide and the sulfur source are completely dried and mixed, and then an organic solvent is added and ground to obtain a sludge-like tetrabasic lead sulfate precursor;
[0011] S2: adding the above organic solvent to the tetrabasic lead sulfate precursor, heating and stirring, and standing to cool;
[0012] S3: filtering the obtained solid, washing it, and drying it to obtain the tetrabasic lead sulfate for the lead-acid battery.
[0013] Furthermore, the organic solvent is mainly composed of ethylene glycol or a combination thereof with polyethylene glycol. The molecular weight of the polyethylene glycol is 200 to 600, and its mass fraction in the organic solvent is ≤20%.
[0014] Further preferably, the organic solvent further comprises a complexing agent with a mass fraction of 0.2 to 1.0%, and the complexing agent is selected from ethylenediaminetetraacetic acid, citric acid, tartaric acid and a combination thereof.
[0015] Furthermore, the amount of the organic solvent used in step S1 is 20-50% of the mass of the solid, and the total amount of the organic solvent used in step S2 is 3-5 times the mass of the solid.
[0016] Furthermore, the sulfur source is selected from lead sulfate, monobasic lead sulfate and mixtures thereof.
[0017] Preferably, the grinding method is ball milling, with a ball-to-material ratio of 5 to 10:1, a rotation speed of 250 to 400 rpm, a grinding time of 1.5 to 3 hours, and the grinding is carried out under nitrogen protection.
[0018] More preferably, the ball mill uses large grinding balls with a diameter of 3 mm and small grinding balls with a diameter of 0.5-0.8 mm, and the number of small grinding balls is 2-10 times that of large grinding balls.
[0019] Preferably, the heating and stirring is carried out at a temperature of 100 to 130° C. and for a time of 30 to 90 minutes.
[0020] Preferably, the static cooling time is 30 to 60 minutes, the cooling target temperature is 70 to 80° C., and the cooling method is thermal oil cooling.
[0021] Preferably, the filtration is performed while hot at 60-80° C., and the washing is performed 2-3 times with acetone, anhydrous ethanol and deionized water respectively.
[0022] The technical solution of the present invention has the following beneficial effects:
[0023] 1. The preparation method of tetrabasic lead sulfate for lead-acid batteries of the present invention adopts wet grinding lubricated by an organic solvent to carry out a semi-solid phase reaction between lead oxide and (monobasic) lead sulfate. Since the organic solvent with ethylene glycol as the main component has lubricity, dispersibility and limited ion mobility, the preparation method is more uniform in mixing, less time and energy consumption cost, and has fewer crystal defects in the product compared with dry grinding. Compared with hydrothermal method or wet grinding, the 4BS obtained by this method has higher selectivity and finer grains.
[0024] 2. In the preparation method described in the present invention, after wet grinding with an organic solvent, a solvothermal reaction is carried out using the same solvent. The ion migration rate is increased in a relatively short period of time through high-temperature stirring, so that the defects of the grains are reduced and the grains develop into long strips without growing too much, thereby achieving the effect of trimming the crystal morphology; the trimmed crystals are not easy to stick together, and the effect of improving the battery cycle life is better. DETAILED DESCRIPTION
[0025] In order to make the technical means, creative features, objectives and effects of the present invention easier to understand, the technical solution of the present invention is further described below. The embodiments involved are only part of the implementation of the present invention and should be understood as an explanation of the technical solution of the present invention rather than a limitation.
[0026] The preparation method of tetrabasic lead sulfate (4BS) for lead-acid batteries of the present invention comprises the following steps:
[0027] S1: The lead oxide and the sulfur source are completely dried and mixed, and then an organic solvent is added and ground to obtain a sludge-like tetrabasic lead sulfate precursor;
[0028] S2: adding the above organic solvent to the tetrabasic lead sulfate precursor, heating and stirring, and standing to cool;
[0029] S3: filtering the obtained solid, washing it, and drying it to obtain the tetrabasic lead sulfate for the lead-acid battery.
[0030] The Pb / S molar ratio of the raw materials is preferably 5.0 to 5.2: 1. The tetrabasic lead sulfate precursor is almost entirely composed of 4BS, but its crystal morphology is still to be refined and has not yet been separated from the solvent, so it is called a precursor.
[0031] Furthermore, the organic solvent is mainly composed of ethylene glycol (EG) or a combination thereof with polyethylene glycol (PEG). The molecular weight of polyethylene glycol is 200 to 600, and the mass fraction of polyethylene glycol in the organic solvent is ≤20%.
[0032] EG and PEG are environmentally friendly, highly lubricating, moderately polar and viscous, and weakly coordinating high-boiling-point solvents. They can reduce cold welding and promote solid dispersion during the grinding stage. During the hot solvent treatment stage, they promote ion migration while inhibiting hydrolysis. They are also less susceptible to local overheating and exhibit low volatility losses. PEG can further inhibit aggregation through steric hindrance, and PEG with a molecular weight below 600 can be used to adjust the solvent's viscosity and can be added selectively in small amounts.
[0033] Further preferably, the organic solvent further comprises a complexing agent with a mass fraction of 0.2 to 1.0%, and the complexing agent is selected from ethylenediaminetetraacetic acid (EDTA), citric acid, tartaric acid and a combination thereof.
[0034] Ethylene glycol and polyethylene glycol, which have hydroxyl or ether bonds, also have weak complexing effects on lead complexes, but they primarily form hydrogen bonds with each other. Adding chelating agents with strong heavy metal complexing strength not only accelerates wet grinding but also improves the efficiency of hot solvent modification of crystal morphology. It is important to note that these complexing agents (especially EDTA) should be used in their acid form rather than their salt form to achieve better solubility in alcohol / ether solvents.
[0035] Furthermore, the amount of the organic solvent used in step S1 is 20-50% of the mass of the solid, and the total amount of the organic solvent used in step S2 is 3-5 times the mass of the solid.
[0036] When grinding at room temperature, the organic solvent has a high viscosity and mainly plays a lubricating role, and can also assist mass transfer at the contact interface; while during high-temperature stirring, the organic solvent mainly plays a dispersing and mass transfer promoting role.
[0037] Furthermore, the sulfur source is selected from lead sulfate, monobasic lead sulfate (1BS) and a mixture thereof.
[0038] Generally speaking, the sulfur source in the technical solution of this invention is lead sulfate. 1BS is relatively expensive, and while it is feasible, it is usually only used as waste for recycling. It is important to note that 3BS, which contains water of crystallization, cannot be used as a sulfur source. As a supplementary note, the other reactant in this invention, lead oxide, must be pure, and cannot be used with lead powder with a certain degree of oxidation as in the hydrothermal method.
[0039] Preferably, the grinding method is ball milling, with a ball-to-material ratio of 5 to 10:1, a rotation speed of 250 to 400 rpm, a grinding time of 1.5 to 3 hours, and the grinding is carried out under nitrogen protection.
[0040] More preferably, the ball mill uses large grinding balls with a diameter of 3 mm and small grinding balls with a diameter of 0.5-0.8 mm, and the number of small grinding balls is 2-10 times that of large grinding balls.
[0041] Ball milling has high rotation speed and produces fine and uniform material, which is suitable for processing nano-level fine particles. However, compared with dry grinding, wet ball milling can still reduce the rotation speed and grinding time while ensuring the material discharge performance.
[0042] Preferably, the heating and stirring is carried out at a temperature of 100 to 130° C. and for a time of 30 to 90 minutes.
[0043] Preferably, the static cooling time is 30 to 60 minutes, the cooling target temperature is 70 to 80° C., and the cooling method is thermal oil cooling.
[0044] Preferably, the filtration is performed while hot at 60-80° C., and the washing is performed 2-3 times with acetone, anhydrous ethanol and deionized water respectively.
[0045] The above temperature is higher than that of a non-pressurized hydrothermal reaction, resulting in a more efficient crystal formation. However, the upper temperature limit must be controlled to ensure the stability of the complexing agent. After the reaction, filtration at a higher temperature is required to ensure uniformity and stability of the solvent (some PEGs have high melting points). Acetone, anhydrous ethanol, and deionized water are successively more polar, effectively washing away residual reactants, organic solvent, and complexing agent.
[0046] The experimental methods are conventional unless otherwise specified, lead oxide (red) and lead sulfate are from Anhui Junma Technology, ethylene glycol is from Ningbo Fude Energy, polyethylene glycol is from Wuhan Jiyesheng, and the remaining reagents are from conventional sources.
[0047] Example 1
[0048] (1) Prepare organic solvent: Mix 708.0 g of ethylene glycol and 77.0 g of polyethylene glycol-600, dehydrate and deoxygenate by nitrogen bubbling, and add 1.5 g of ethylenediaminetetraacetic acid and 2.5 g of citric acid to fully dissolve.
[0049] (2) Mechanical grinding: 147.2 g of lead oxide and 50.0 g of lead sulfate were vacuum dried for 30 min and mixed, 70 g of the organic solvent prepared in step (1) was added, and then ball milled at 350 rpm for 2 h (ball-to-material ratio 8:1, ball diameter 3 mm:0.6 mm = 1:5) to obtain a muddy precursor.
[0050] (3) Hydrothermal finishing: Add all the remaining organic solvents to the precursor, heat to 115 °C in the reactor and stir for 60 min, then add heat transfer oil through the jacket and cool to 75 °C in 45 min.
[0051] (4) Post-treatment: The reaction solution is filtered while hot (above 60°C throughout the process), then washed three times with acetone, anhydrous ethanol and deionized water respectively, and finally dried at 90°C to obtain tetrabasic lead sulfate product.
[0052] Inductively coupled plasma mass spectrometry (ICP-MS) analysis showed that the Pb / S ratio of the product was 4.9763 and the purity was 99.41% (impurities were calculated as PbSO4); SEM imaging showed that the product was rod-shaped with an average diameter of 85 nm and an average length of 740 nm.
[0053] Example 2
[0054] (1) Prepare organic solvent: 803.6 g of ethylene glycol and 200.9 g of polyethylene glycol-200 are mixed, dehydrated and deoxygenated by nitrogen bubbling, and 3.0 g of citric acid and 7.0 g of tartaric acid are added to fully dissolve.
[0055] (2) Mechanical grinding: 150.9 g of lead oxide and 50.0 g of lead sulfate were vacuum dried for 30 min and then mixed. 100 g of the organic solvent prepared in step (1) was added, and then ball milled at 400 rpm for 1.5 h (ball-to-material ratio of 5:1, ball diameter 3 mm:0.8 mm = 1:2) to obtain a sludge precursor.
[0056] (3) Hydrothermal finishing: Add all the remaining organic solvents to the precursor, heat to 130 °C in the reactor and stir for 30 min, then add heat transfer oil through the jacket and cool to 80 °C in 30 min.
[0057] (4) Post-treatment: The reaction solution is filtered while hot (above 60°C throughout the process), then washed three times with acetone, anhydrous ethanol and deionized water respectively, and finally dried at 90°C to obtain tetrabasic lead sulfate product.
[0058] Inductively coupled plasma mass spectrometry (ICP-MS) analysis showed that the Pb / S ratio of the product was 5.0062 and the purity was 99.38% (impurities were calculated as PbO); SEM imaging showed that the product was rod-shaped with an average diameter of 110 nm and an average length of 680 nm.
[0059] Example 3
[0060] (1) Prepare organic solvent: 611.4 g of ethylene glycol, dehydrate and deoxygenate by nitrogen bubbling, add 1.3 g of ethylenediaminetetraacetic acid and fully dissolve.
[0061] (2) Mechanical grinding: 139.1 g of lead oxide, 30.0 g of lead sulfate, and 34.7 g of monobasic lead sulfate were vacuum dried for 30 min and mixed. 45 g of the organic solvent prepared in step (1) was added, and then ball milled at 250 rpm for 3 h (ball-to-material ratio 10:1, ball diameter 3 mm:0.5 mm = 1:10) to obtain a sludge precursor.
[0062] (3) Hydrothermal finishing: Add all the remaining organic solvents to the precursor, heat to 100 °C in the reactor and stir for 90 min, then add heat transfer oil through the jacket and cool to 70 °C in 60 min.
[0063] (4) Post-treatment: The reaction solution is filtered while hot (above 60°C throughout the process), then washed three times with acetone, anhydrous ethanol and deionized water respectively, and finally dried at 90°C to obtain tetrabasic lead sulfate product.
[0064] Inductively coupled plasma mass spectrometry (ICP-MS) analysis showed that the Pb / S ratio of the product was 5.0098 and the purity was 99.03% (impurities were calculated as PbO); SEM imaging showed that the product was rod-shaped with an average diameter of 70 nm and an average length of 760 nm.
[0065] Comparative Example 1
[0066] The only difference between this comparative example and Example 1 is that the organic solvent is replaced with an equal amount of deionized water containing the same concentrations of EDTA and citric acid. XRD verification shows that the product contains no less than 40% by mass of 3BS.
[0067] Comparative Example 2
[0068] In this comparative example, based on Comparative Example 1, the mechanical grinding conditions were modified to: a rotation speed of 500 rpm and a grinding time of 5 hours. Inductively coupled plasma mass spectrometry (ICP-MS) analysis revealed a Pb / S ratio of 4.8750 and a purity of 96.88% (implant calculation as PbSO4). SEM imaging revealed the product to be short rods with an average diameter of 2.8 μm and an average length of 7.6 μm.
[0069] Comparative Example 3
[0070] The only difference between this comparative example and Example 1 is that no solvent is added during the mechanical grinding stage. XRD verification shows that the product contains PbO in a mass percentage of not less than 20%.
[0071] The performance of the tetrabasic lead sulfate seed crystals obtained in Examples 1 to 3 and Comparative Example 2 was tested:
[0072] A 3-D-180 lead-acid battery positive electrode lead paste was prepared at 60°C, with 1 wt% of 4BS seed crystals prepared in each example and comparative example added. A blank control was made without 4BS. The lead paste was applied to the electrode plate surface and cured at 75°C for 8 hours to form the positive plate. The lead-acid battery was assembled with matching negative plates in an alternating arrangement of 9 positive and 10 negative plates. A three-stage charge / constant current discharge cycle was used to test the initial capacity and cycle life (expressed as the number of cycles required for 30% capacity decay). The test results are shown in Table 1.
[0073] Table 1 Initial capacity and cycle life of lead-acid batteries
[0074]
[0075] The test results of the properties of each group of 4BS products show that the preparation method described in the present invention can produce 4BS grains with a relatively small particle size, high purity, and a certain aspect ratio. If the organic solvent is replaced with water during the grinding stage, a high proportion of by-products such as 3BS is obtained in a short time, and after a long period of grinding, coarse 4BS grains with a low aspect ratio are obtained. If dry grinding is performed, the reaction cannot be fully achieved within the same grinding speed and time.
[0076] Analysis of the effects of each group of 4BS products on the battery, including but not limited to the addition of a small amount of positive electrode lead paste as a seed crystal, shows that the 4BS prepared by the present invention has a lower impact on the initial capacity of the battery and has a more significant improvement in cycle life than larger and coarser products.
[0077] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the embodiments. Those skilled in the art will appreciate that other variations or modifications may be made based on the above description, and such obvious variations or modifications should still be considered within the scope of protection of the present invention.
Claims
1. A method for preparing tetrabasic lead sulfate for lead-acid batteries, characterized in that: The steps include: S1: The lead oxide and the sulfur source are completely dried and mixed, and then an organic solvent is added and ground to obtain a sludge-like tetrabasic lead sulfate precursor; S2: adding the above organic solvent to the tetrabasic lead sulfate precursor, heating and stirring, and standing to cool; S3: filtering the obtained solid, washing it, and drying it to obtain the tetrabasic lead sulfate for the lead-acid battery.
2. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to claim 1, wherein: The organic solvent is mainly composed of ethylene glycol or a combination of ethylene glycol and polyethylene glycol; the molecular weight of the polyethylene glycol is 200-600, and the mass fraction of the polyethylene glycol in the organic solvent is ≤20%.
3. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to claim 2, wherein: The organic solvent further comprises a complexing agent with a mass fraction of 0.2 to 1.0%, and the complexing agent is selected from ethylenediaminetetraacetic acid, citric acid, tartaric acid and a combination thereof.
4. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to any one of claims 1 to 3, characterized in that: The amount of the organic solvent used in step S1 is 20-50% of the mass of the solid, and the total amount of the organic solvent used in step S2 is 3-5 times the mass of the solid.
5. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to claim 1, wherein: The sulfur source is selected from the group consisting of lead sulfate, monobasic lead sulfate and mixtures thereof.
6. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to claim 1, wherein: The grinding method is ball milling, the ball-to-material ratio is 5-10:1, the rotation speed is 250-400 rpm, the grinding time is 1.5-3 hours, and the grinding is carried out under nitrogen protection.
7. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to claim 6, wherein: The ball mill uses large grinding balls with a diameter of 3 mm and small grinding balls with a diameter of 0.5-0.8 mm, and the number of small grinding balls is 2-10 times that of large grinding balls.
8. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to claim 1, wherein: The heating and stirring temperature is 100-130° C., and the heating and stirring time is 30-90 minutes.
9. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to claim 1, wherein: The static cooling time is 30 to 60 minutes, the cooling target temperature is 70 to 80° C., and the cooling method is thermal oil cooling.
10. The method for preparing tetrabasic lead sulfate for lead-acid batteries according to claim 1, wherein: The filtration is performed while hot at 60-80° C., and the washing is performed with acetone, anhydrous ethanol and deionized water respectively for 2-3 times.
Citation Information
Patent Citations
Preparation method of nanometer four-alkali lead sulfate
CN103928685A
High-purity ultra-fine tetrabasic lead sulfate product and preparation method thereof
CN109867302A
Preparation method and device of high-purity tetrabasic lead sulfate
CN114538503A
